Willow biomass and cuttings' production potential over ten successive annual harvests. (October 2017) - Stolarski, Mariusz J.; Szczukowski, Stefan; Tworkowski, Józef; Krzyżaniak, Michał; Załuski, Dariusz
Abstract: Willow nursery plantations for cuttings' production, which provide planting material for new, improved varieties, can be set up in greater densities and must be harvested in one-year cycles. Therefore, the aim of this study was to determine the effect of planting density on the survival rate, yield and production potential of cuttings of two varieties and three clones in ten successive one-year harvest cycles. The experiment was conducted in the years 2004–2013 in northern Poland. Significant differentiation regarding the biomass yield and the number of cuttings was demonstrated not only between the planting densities, but also between the varieties/clones and the interactions between those factors. The final survival rate was close to 85% with a planting density of 12 000 ha −1 and 24 000 ha −1 . However, the survival rate was half that at the highest planting density. The varieties and clones differed in their morphological features, which affected their yield, both as chips and cuttings number. The best results were achieved for the UWM 095 clone and the Tur variety. The yield varied over the next ten years, but it was not found to decrease as the plantation aged. An increase in planting density from 12 000 ha −1 to 24 000 ha −1 resulted in greater yield, but a further increase to 48 000 ha −1 and 96 000 ha −1 did not bring such effects. The production of cuttings could bring more than 20 times higher potential income compared to the production of chips for energy purposes. Highlights: Willow nursery plantations can be successfully utilised for at least ten years. Dry matter yield was highly depended on planting density and on variety. The best results were achieved for the UWM 095 clone and the Tur variety. Cuttings could bring more than 20 times higher income than chips for energy. On average, 30 ha of willow could be set up from 1 ha of a nursery plantation.